Preliminary studies on crop-weather relationships - Cotton (MAUSAM, 1960)
Under the All India Crop-Weather Scheme —Cotton, quantitative observations, on a uniform basis, are being recorded at a network of selected experimental farms in India, regarding the growth and yield and the incidence of diseases and pests of cotton crop, side by side with the weather factors experienced by the crop during its life-cycle. The object of the scheme is to formulate, in quantitative terms, the effects of the different weather factors on the growth and yield and the incidence of diseases and pests of the cotton crop. However, a study of the data using standard statistical techniques can be undertaken only after these have been collected for a sufficiently long period, i.e., 25 to 30 years. Meanwhile, a tentative study of the data collected up to the year 1955-56 was made, to obtain indications, though of a strictly tentative nature, of crop-weather relationships pertaining to the cotton crop. An account of these studies was included in the Report of the Co-ordinated Crop-Weather Scheme relating to Cotton, for the year 1956-57, by the Director, Agriculture Meteorology, Poona. It is considered that the results obtained are of sufficient general interest to the scientific public and hence these are described in this paper.